2008
DOI: 10.1111/j.1751-553x.2007.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

The JAK2V617F tyrosine kinase mutation identifies clinically latent myeloproliferative disorders in patients presenting with hepatic or portal vein thrombosis

Abstract: Clinically latent myeloproliferative disorders (MPDs) are important causes of what would otherwise be considered idiopathic hepatic (HVT) or portal vein thrombosis (PVT). They may be difficult to diagnose initially because the peripheral blood count may be normal at the time of thrombosis. A strong association between an activating mutation of the gene encoding one of the Janus kinase family of tyrosine kinases (JAK2(V617F)) and the Philadelphia chromosome-negative MPDs has been identified. We have studied 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Twenty-four studies were therefore included in this systematic review. 10,21,23,25,27,30,33,37,[40][41][42][43][44][45][46][47][48][49]51,52 Interobserver agreement for study selection was excellent ( ϭ 0.96).…”
Section: Study Identification and Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-four studies were therefore included in this systematic review. 10,21,23,25,27,30,33,37,[40][41][42][43][44][45][46][47][48][49]51,52 Interobserver agreement for study selection was excellent ( ϭ 0.96).…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…Studies ranged in size from 11 to 560 patients; a total of 3508 patients were included. Six case-control studies 10,23,25,27,35,40 and 18 retrospective cohort studies 21,24,30,31,34,36,37,[41][42][43][44][45][46][47][48][49]51,52 were included in our systematic review. Five studies enrolled patients consecutively.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 JAK2 V617F was seen in 38-43% of splancnic vein thrombosis with normal or low blood counts and in 18-37% of portal vein thrombosis. 22 In another study, JAK2 mutation was found in 74% of 19 idiopathic portal or hepatic vein thrombosis and JAK2 mutation was reported as a valuable genetic marker in latent MPD diagnosis. 23 In a study, ET patients with JAK2 V617F mutation were found to have higher Hb, neutrophile levels than patients without the mutation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that JAK2 (V617F) mutation is present in 50-79.3 % all cases of diagnosed MPN with SVT. On the other hand, in patients with latent MPN with SVT, the incidence of JAK2 (V617F) mutation varies from 11 to 74 % [13][14][15][16][17][18][19][20][21][22][23]. Only one retrospective study reported a low prevalence rate of 9.3 % [24].…”
Section: Jak2 (V617f) Mutation Myeloproliferative Neoplasms and Splementioning
confidence: 99%